Effect of 82% Lactic Acid in Treatment of Melasma. (17th July 2014) - Singh, Rashmi; Goyal, Sapna; Ahmed, Qazi Rais; Gupta, Narendra; Singh, Sujata
Abstract : Melasma is an acquired, chronic, and symmetrical hypermelanosis, characterized by brown patches of variable darkness on sun exposed areas of body. There are numerous modalities of treatment currently in use for this disease, of which the chemical peeling is very commonly used. Therefore, the present work was done to see the effect of 82% lactic acid peel in the treatment of melasma. A total number of 20 patients of either sex attending the OPD of dermatology department with clinically evident melasma were included in the study. 82% Lactic acid peel was applied on the face for 12 weeks in each patient. Patients were evaluated clinically and photographically at various intervals and in follow-up till 24 weeks. Assessment of patient satisfaction and side effects were also noted. All the subjects completed the study. Application of this peel for 12 weeks significantly decreased the melasma area severity index score and also melasma severity scale score. Patient and physician analogue scales also showed the improvement by the treatment. Regarding the adverse effects, burning sensation was the only side effect noted in our study. In conclusion, 82% lactic acid peel is well tolerated and can be used for the treatment of melasma.